Radio media planning and its role in the success of the Algerian sports programs (Radio Algeria from M’sila model) - bachir, abdelhak; dahmani, Naima; zahaf, Mohammed (sports creativity, 2025)
The aim of this study is to highlight the importance of the role of radio media planning in the Algerian radio station in M'sila Regional station in raising the efficiency and level of sports programs and their success through the established goals and the approved program network and the methods and types of artistic expressionist press. To achieve this, the researcher used the descriptive approach to suit this study On a target sample of 20 workers where a questionnaire form was distributed and based on the opinions of the radio workers that the media planning plays a large and effective role for the success of the Algerian radio programs. The researcher needs to prepare the climate of coordination more in the local radio to ensure the successful planning responds to and consistent with the goals that must be related to the needs of the public and his inclination